Digital-Based Interactive Teaching Module for Prospective Teachers: SBdP Learning Supplement to Improve Elementary School Student Learning Outcomes - Antosa, Zariul; Fendrik, Muhammad; Anggriani, Mitha Dwi; Munjiatun, (Jurnal Paedagogy, 2026)
This study aims to develop and evaluate the feasibility, practicality, and effectiveness of digital-based interactive teaching materials for Arts, Culture, and Crafts (SBdP) learning in elementary schools. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research participants included three expert validators, five SBdP teachers, and students from two elementary schools. The instruments used in this study comprised expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test assessments of learning outcomes. The data were analyzed using descriptive statistics, normality testing (Kolmogorov–Smirnov), homogeneity testing (Levene’s test), a paired-sample t-test, and normalized gain (N-gain) analysis. The findings indicate that the developed interactive teaching materials are highly feasible across all assessed aspects, including content, language, graphics, didactics, construction, and technical quality. Teacher evaluations categorized the materials as very good, while students reported that they were easy to use, engaging, and helpful in improving conceptual understanding. The effectiveness test revealed a significant improvement in learning outcomes in both schools, with mean scores increasing from 45.60 to 74.70 and from 38.22 to 71.38, respectively. The hypothesis testing results showed that F_count > F_table, indicating a statistically significant difference. Furthermore, the N-gain analysis demonstrated that most students achieved a moderate level of improvement. In conclusion, the developed digital-based interactive teaching materials are valid, practical, and effective in enhancing SBdP learning outcomes in elementary schools.